(untitled) (Sudurpaschim Spectrum, 2024)
Remittance inflow is taking greater size than the other capital inflow in Nepal. It has multidimensional effects on the economy. However, its impact on private sector credit is absent. Hence, this paper analyses the effects of remittances on private sector credit in Nepal taking time series data spanning from 1975 to 2021. Alongside remittances as the key explanatory variable, other control explanatory variables such as gross investment, total trade, real gross domestic product, the national consumer price index, and foreign aid were considered. Unit root analysis revealed that all variables were integrated at order one. Consequently, a cointegration test was conducted, indicating the presence of at least one cointegration equation. Subsequently, an ordinary least squares regression was performed using first difference data. The results were subjected to various econometric diagnostic tests, including assessment for autocorrelation, heteroscedasticity, multicollinearity, normality, as well as the Durbin–Watson test, t-tests for coefficients, and the F-test. Both the coefficient of determination and the adjusted coefficient of determination confirmed that the models were well-fitted. The outcomes of the model suggest that remittances have a positive impact on the enhancement of the private sector credit. Based on these findings, the study indorses implementing policies aimed at heightening remittance inflows into the country to further financial development in Nepal, specifically promoting private sector credit.